Endophytic bacteria of Anisophyllea disticha (Raja Berangkat) from tropical lake environment in Malaysia - Zainal Abidin, Zaima Azira; Zolkeflia, Nurhasliza; Shahari, Rozilawati; Khan Chowdhury, Ahmed Jalal (Desalination Publication, 2020)
Lake Kenyir is the largest artificial lake in South East Asia and serves as habitats for diverse flora and fauna. Moreover, Lake Kenyir is a rich resource of medicinal plants which has been used by local community surrounding the lake. Endophytic bacteria are able to colonize plants without causing harm and they can be highly beneficial towards their plant hosts. The aim of this study is to isolate and identify endophytic bacteria from the leaves and roots of a medicinal plant, Anisophyllea disticha (Raja Berangkat), and to evaluate their antimicrobial capabilities. Twenty isolates each from the leaves and roots were randomly selected for molecular identification using 16S rRNA gene. Partial 16S rRNA gene sequences revealed that genus Bacillus dominated the endophytic bacteria from the leaves with two isolates belonging to Paenibacillus and Aeribacillus. Five genera namely, Bacillus, Staphylococcus, Lysinibacillus, Paenibacillus, and Mycobacterium were successfully obtained from the roots of A. disticha. Nine endophytic bacteria—five Bacillus species (R3, R11, R13, R26, R37), Lysinibacillus (R9), two Staphylococcus species (R6, R27) and Mycobacterium species (R33) from roots were found to show weak antibacterial and/or antifungal activities. Findings from this study provide an insight to endophytic bacteria inhabiting A. disticha and the role they may play in their plant host.